Drawback: a ampliação do benefício no Brasil como estratégia política, econômica e social para a ascensão do Sul Global no Sistema Internacional (Direito e Humanidades, 2025)
The aim of this article is to analyze the extension of the drawback benefit for companies that participate in international private organization tenders, understanding the foundations of the regime, as well as the legal discussions on the subject. In order to achieve the proposed objective, an analysis was made of the positions on the subject, as well as the changes over time, which have led to new laws, decrees and court positions. After analyzing the data collected, it was observed that, over time, the benefit has been expanded so that it can exercise its political, social and economic function for which it was created. In this sense, the ruling analyzed in this paper, which was that the drawback system should be granted to companies, even private ones, that participate in international tenders for private organizations.